Teaching Narrative Text Using TAI Method To Increase Students' Writing Ability - Rahmanita Zakaria; Muhammad Hasyimsyah Batubara; Kurniati Bukit (Asosiasi Dosen Perguruan Tinggi Islam, 2021)
The research is the teaching narrative text using team assisted individualization (TAI) method to increase students' writing ability at second years SMPN 31 Takengon. The researcher used quantitative research with experimental design. The second year of SMPN 31 Takengon (VIII1 and VIII2) as the sample. Technique data analysis in this investigation uses statistics with the score t-test and formulate uses to compare the actual difference between control and experimental samples. The result of the using the team-assisted individualization (TAI) method is increase the students' writing in narrative text. It can be seen from the result of test tobs > ttable value tobs 2.88 and ttable 1,60 or tobs ? ttable. The team-assisted individualization (TAI) method also helps the students increase imagination and make the students easy to write in narrative text.